Bank Lending : Principles and practice. - Lee, Nirmala (Gosbrook Professional Publishing Ltd, 2018)
This book is for students and professionals working, or intending to work, in a lending-related role. It provides comprehensive, up-to-date coverage of bank lending and will give lending staff the detailed knowledge and understanding of the financial and legal aspects of their roles they need to fulfil employer, as well as customer, expectations.